Spiders as potential aphid predators in eastern Colorado agroecosystems - Kerzicnik, Lauren M., author; Peairs, Frank B., advisor; Cushing, Paula E., advisor; Hufbauer, Ruth A., committee member; Peterson, Gary, committee member (Colorado State University. Libraries, 2011)
Spiders are indigenous, ubiquitous natural enemies that have been associated with reduced pest densities and may be particularly useful in reducing aphid densities. Diuraphis noxia is an important economic pest in wheat agroecosystems in Colorado. Therefore, it is critical to determine the spider fauna within these agroecosystems, spiders that may be key biological control agents for conservation, and determine if alternative cropping systems can enhance or maintain these particular spider species. The inclusion of sustainable agricultural systems is an important component of integrated pest management. The faunal composition of spiders in eastern Colorado agroecosystems was described and analyzed to determine whether a crop-intensified system resulted in greater spider density and biodiversity than a conventional system. Three sites in eastern Colorado-Akron, Briggsdale, and Lamar-were studied. From 2002-2007, 11,207 spiders from 17 families and 119 species were collected from pitfall, vacuum, and lookdown sampling techniques. Crop intensification had little effect on spider density or biodiversity. Spider mean densities/activity densities and biodiversity were low for all years and sites, with the exception of 2005 and 2006. At all sites, the fauna was dominated by hunting spiders in the Lycosidae and Gnaphosidae families (72%), which differs from the dominance of web-building spiders in western European agroecosystems. Before establishing whether predators can contribute to the biological control of a pest, it is important to determine the availability of the pest for prey. Thus, the falling rate of D. noxia from wheat infested at 1x and 10x aphid infestation levels and resistant and susceptible varieties was measured. Falling rates ranged from 0.7% to 69.5% in Fort Collins, CO, and from 1.4% to 59.5% in Akron, CO. The falling rate of D. noxia was more influenced by plant growth stage than aphid densities, with the highest falling rate occurring prior to wheat senescence. Resistant wheat plants did not have increased aphid falling rates. The falling rate of D. noxia was highest at lower aphid densities, thus epigeal predator consumption of D. noxia can occur at lower aphid densities. Nevertheless, the falling rate of D. noxia clearly indicates that these prey can represent an important food source for ground predators. It is the conservation of key species and not necessarily the conservation of predators per se that is important for effective biological control. Therefore, it is critical to identify which predators are consuming pests in the field. Species-specific primers and the polymerase chain reaction were used to determine if two dominant spiders, Tetragnatha laboriosa and Pardosa sternalis, were consuming D. noxia DNA in the field. A partial 1146 bp sequence from the mitochondrial cytochrome oxidase I (COI) gene was used and aligned with other non-target sequences to create two primer pairs that amplified a 227 bp fragment of D. noxia DNA. A total of 64 and 71 T. laboriosa and P. sternalis, respectively, were collected from within three D. noxia infestation levels-0x, 1x, and 10x- in Fort Collins, CO, from May-July at the following wheat stages: boot, inflorescence, anthesis, milk, and dough. Of the spiders collected in the field, 32% and 48% of T. laboriosa and P. sternalis tested positive for D. noxia DNA. Additionally, 92% of T. laboriosa were collected at the 1x or 10x D. noxia infestation levels combined, which indicated that T. laboriosa responded to increased D. noxia densities. Pardosa sternalis, however, was more evenly distributed within aphid infestation levels.
Keywords: crop intensification; diversity; gut-content; wheat; Araneae; Diuraphis noxia